Estrés Laboral Y Afectación Psico-FÃsica En El Rendimiento Del Personal En Un Call Center Policial, Quito-Ecuador - Brito, Pedro Flores; Rosero, Shirley Fernanda; Reinoso, Daniel Renato (European Scientific Journal, ESJ, 2018)
The study investigates the various aspects of the perception of the health of call-center workers. This paper focuses on identifying the psychophysical affectation in the work performance of workers due to work stress from the foundation of preventive health. This, however, associated the relationship between the two variables to verify its affectation. Occupational stress influences the occurrence of psycho-physical alterations that affect work performance. This is attributed to the fact that it was found in the group investigated, which is composed of workers of the police operational management center of the metropolitan district of Quito (CGOP). The Maslach universal test that measures Burnout syndrome, emotional fatigue, depersonalization, and personal fulfillment were combined with attitude tests with Likert scales that measure the perception of those involved with their psychophysical affectation at their place of work. The results are evidenced, according to the Maslach test, in relation to the suffering of Burnout syndrome. The result shows that in this study, no worker meets the three conditions: emotional exhaustion (10.5%), depersonalization (22.2%), or realization personal (22.3%). However, they do meet one of the three areas individually. Associated with stress, physical-psychological affectations were identified, especially in the nervous system (1 in 10) and to a lesser extent in the digestive system. In conclusion, the results are mostly isolated because the study group performs frequent physical activity, which considerably diminishes the secondary and negative effects on their physical health.